Doğurganlığın Düzenlenmesi - Aydın, Ruveyde; Aktaş, Songül; Uludağ, Elif; Özkan, Sevgi; Dağdelen, Derya; Zincir, Handan; Aydın Beşen, Meltem; Aygör, Hamide; Kıyak, Sibel; Alan Dikmen, Hacer; Yücesoy, Hüsne; Erbil, Nülüfer; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-